2021
DOI: 10.1021/acs.jafc.1c03115
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition Profiling and Biological Activities of Phenolic Compounds in Eleven Red Sorghums

Abstract: The profiles of soluble and insoluble phenolic compounds in 11 commercial red sorghums (B11, B12, B13, B14, J124, J127, J138, J140, J142, J152, and J158) were investigated using ultraperformance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF-MS) analysis. A total of 48 phenolic compounds including 35 phenolic acids and their derivatives, 12 flavonoids, and 1 proanthocyanidin were identified, and 8 phenolic compounds were reported for the first time in sorghums. Four ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…Similarly, the associations of TTC to DPPH • scavenging activity (r = 0.95), ABTS •+ scavenging activity (r = 0.97), and FRAP (r = 0.98) were strong and significant ( p < 0.001). The positive and significant correlations of TTC and TPC to each of the antioxidant activities demonstrate the roles of tannins and phenols in regulating ROS and RNS, which corroborate multiple other studies ( 4 , 11 , 39 ). In contrast, TTC, TPC, and antioxidant activities showed negative and/or weak correlations with individual fatty acids which could be the result of their distinct biosynthesis routes ( 54 , 59 ).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Similarly, the associations of TTC to DPPH • scavenging activity (r = 0.95), ABTS •+ scavenging activity (r = 0.97), and FRAP (r = 0.98) were strong and significant ( p < 0.001). The positive and significant correlations of TTC and TPC to each of the antioxidant activities demonstrate the roles of tannins and phenols in regulating ROS and RNS, which corroborate multiple other studies ( 4 , 11 , 39 ). In contrast, TTC, TPC, and antioxidant activities showed negative and/or weak correlations with individual fatty acids which could be the result of their distinct biosynthesis routes ( 54 , 59 ).…”
Section: Resultssupporting
confidence: 89%
“…In a typical way, IS8017 simultaneously displayed the highest levels of both luteolin (1.67 mg/g) and apigenin (6.35 mg/g). High concentrations of 3-deoxyanthocyanidins and flavonoids in sorghum seeds have attracted attention for their pronounced health benefits and disease protection, as well as for their potential use as food colorants ( 4 , 9 , 14 , 27 ). The breeding lines with high 3-deoxyanthocyanidins contents, particularly Gangwonsususu 6, JN69, JN 36, IS8089, and IS8123, may therefore be valuable resources.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, the TPC of SPs in FF and FP was 8.721 and 17.679 µmol FAE/g DS, respectively, and the TPC of IBPs in FF and FP was 7.544 and 12.903 µmol FAE/g DS, respectively. It can be observed that the TPC values of soluble fraction were higher than those of the insoluble fraction, whether in FF or FP of CFG, which is in agreement with previous studies of mistletoes [9] and red sorghums [17]. In addition, these results suggest that polyphenol molecules were more enriched in the FP than in the FF.…”
Section: Total Phenolic Content (Tpc) and Total Flavonoid Content (Tfc)supporting
confidence: 91%
“…Flavonoids are the main compounds related to the sorghum pericarp color variation, especially anthocyanins and condensed tannins subclasses . Li et al found that the antioxidant capacity and total phenolic and flavonoid contents were similar among 11 genotypes of red sorghums. They also found that condensed tannins were significantly higher in soluble (free) fractions than in insoluble (bound) ones.…”
Section: Resultsmentioning
confidence: 99%